Job performance and mediating role of employee retention in private Institutions of Higher Education - Lee, S.T.; Chong, C.Y. (2017)
Higher education is no longer an option but a necessity. Private Higher Education Institutions (PHEIs) in Malaysia is a destination for both local and international students, in which the focus is on creation on knowledge workers for the country. The number of PHEIs and student enrolment increases yearly as spaces in the public universities are scarce. For quality assurance, high staff turnover has always been a concern in PHEIs. Hence, the purpose of this study is to explore the factors affecting job performance and the mediating effect of employee engagement for both academic and non-academic staff. A quantitative, self-administered questionnaire was used in this research. 200 respondents from the top ten PHEIs participated in this study. Career development, employee engagement, work-life balance and employee retention were found to have significant relationship with job performance. Hierarchical re- gression analysis proves that employee retention fully mediates the relationship between career development and job performance, as well as work-life balance and job performance. However, there is no mediation effect of employee retention on employee engagement and job performance.